Thermal optimized PCR coupled to CRISPR-Cas12a for rapid detection of blaOXA-1 resistance gene - Ana Quiroz-Huanca; Maryhory Vargas-Reyes; Juan Diego López; Kiara Flores-Jimenez; Sofia Saldarriaga-Morán; Karla Cifuentes; Roberto Alcántara (PLoS ONE, 2026)
The β-lactams are critically important broad-spectrum antibiotics, widely used as first-line treatments; however, their effectiveness is increasingly compromised by β-lactamase enzymes. Among these, OXA-type enzymes have expanded to over 400 variants and are highly prevalent in Enterobacteriaceae . Current phenotypic and molecular detection tests have long turnaround times or require specialized equipment, respectively. In this study, we optimize a rapid molecular assay combining a PCR with modified thermal ramp rate (TRR) along with CRISPR-Cas12a fluorescence detection for bla OXA-1 -harboring E. coli isolates. Using a commercial DNA Taq polymerase (TRR: 2.2 °C/s, annealing and extension hold time: 1 s), amplification time was reduced from 80 to 30 min, enabling detection within 50 min (PCR: 30 min; CRISPR: 20 min). With a locally produced enzyme (hold: 10 s), amplification time was 44 min. To demonstrate the practical application of the assay, we evaluated spiked poultry fecal samples achieving an analytical sensitivity of 8 CFU/reaction using commercial DNA Taq polymerase. The accelerated PCR:CRISPR workflow delivers results in less than one hour without compromising technical sensitivity (attomoles range), not requiring high technical expertise, and can be implemented in laboratories with basic molecular biology equipment.